A council of dolls : a novel - Power, Mona Susan, 1961- (Mariner Books, 2023)
"A Council of Dolls is the moving and unforgettable new novel from PEN Award-winning Sioux author Mona Susan Powers, spanning four generations of Yanktonai Dakota women from the 19th century to the present day"--